2011
DOI: 10.1021/es1033553
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH on Aqueous Se(IV) Reduction by Pyrite

Abstract: International audienceInteraction of aqueous Se(IV) with pyrite was investigated using persistently stirred batch reactors under O2-free (<1 ppm) conditions at pH ranging from 4.5 to 6.6. Thermodynamic calculations, an increase in pH during the experiments, and spectroscopic observation indicate that the reduction of aqueous Se(IV) by pyrite is dominated by the following reaction: FeS2 + 3.5HSeO3− + 1.5H+ = 2SO42− + Fe2+ + 3.5Se(0) + 2.5H2O. The released Fe(II) was partitioned between the bulk solution and pyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(55 citation statements)
references
References 39 publications
2
53
0
Order By: Relevance
“…These facts are consistent with the reduction of Se(IV) to Se(0) (Kang et al, 2011 (Fig. 4) Descostes et al (2004) reported values ranging from 1.25 at pH 1.5 to 1.6 at pH 3, while Kamei and Ohmoto (2000) obtained values in the range 0.93-2.00 for the same reaction at pH 5.7 ± 0.3.…”
Section: Pyrite Dissolutionsupporting
confidence: 89%
See 2 more Smart Citations
“…These facts are consistent with the reduction of Se(IV) to Se(0) (Kang et al, 2011 (Fig. 4) Descostes et al (2004) reported values ranging from 1.25 at pH 1.5 to 1.6 at pH 3, while Kamei and Ohmoto (2000) obtained values in the range 0.93-2.00 for the same reaction at pH 5.7 ± 0.3.…”
Section: Pyrite Dissolutionsupporting
confidence: 89%
“…In a previous work we found that, in the presence of unreduced selenite, Se(0) rather than iron selenides can be formed on Fe(II)-bearing minerals (Kang et al 2013). Therefore, the iron decrease can be attributed to the formation of Fe(OH) 3 (Kang et al, 2011), in agreement with XPS results (Fig. A.6), while, at the same time, additional pyrite was decomposed through reaction (1) leading to the release of more aqueous S (see Section 3.4 in the following).…”
Section: Pyrite Dissolutionmentioning
confidence: 90%
See 1 more Smart Citation
“…18−20 Framboids are difficult to synthesize in the laboratory, 39 and no experimental evidence on Se-framboidal interactions is available. Some experimental studies used iron sulfides (e.g., mackinawite, 42 pyrite [18][19][20]43 ) and sorbed Se onto them. When synthetic pyrite was used, the Se was coreduced leading to the formation of ferroselite FeSe(-I) x .…”
Section: Environmental Science and Technologymentioning
confidence: 99%
“…Selenium had been considered to migrate as soluble SeO 3 2− /SeO 4 2− because of its slow reduction kinetics [53][54][55][56], in spite of thermodynamic stability of Se(−II) under reducing disposal conditions. Recent works have demonstrated the abiotic reduction of Se(IV) and Se(VI) to Se(0) by several Fe(II)-bearing minerals [24,[55][56][57][58][59][60][61][62] and to Se(−II) by Fe(0) nanoparticles [63]. Understanding the sorption behavior of Se(−II) species is important; however, the sorption data of Se(−II) are scarce because of the experimental difficulties of maintaining the reducing state of Se.…”
mentioning
confidence: 99%